Energy Tax Exemptions and Industrial Production - Andreas Gerster; Stefan Lamp (Center for Economic Studies and ifo Institute (CESifo), 2023)
Environmental policies are often accompanied by exemptions for energy-intensive and trade-exposed industrial firms to avoid leakage from regulated to unregulated jurisdictions. This paper investigates the impact of a large electricity tax exemption on production levels, employment, and input choices in the German manufacturing industry. For two different policy designs, we show that exempted plants significantly increase their electricity use. This effect is considerably larger under a notched exemption policy, where passing an eligibility threshold yields infra-marginal benefits, compared to a revised policy where these benefits have been largely removed. We de-tect no significant impact of the exemptions on production levels, export shares, and employment. Using counterfactual simulations, we document substantial distortive effects of notched exemption policies when financial stakes are high and compliance cost for firms are low.
Keywords: D22; H23; L60; Q41; 330; environmental policy; leakage; energy taxes; manufacturing industry